2022
DOI: 10.1007/s12519-022-00650-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and clinical efficacy of linezolid in children: a systematic review and meta-analysis

Abstract: Background We aimed to evaluate the tolerability and efficacy of linezolid in children for treating suspected and diagnosed Gram-positive bacterial infections. Methods A systematic literature search was conducted up to April 23, 2021, using linezolid and its synonyms as search terms. Two reviewers independently identified and extracted relevant randomized controlled trials and prospective cohort studies. The extracted studies were included in a single-rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…This nding aligns with previous literature highlighting linezolid's potential to induce thrombocytopenia in neonates and pediatric populations [32][33][34]47]. Despite the widespread use of linezolid in clinical practice, there is no consensus on the incidence of its hematological toxicity in pediatrics, and the rates vary markedly from country to country, possibly due to ethnic differences [31][32][33][34].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This nding aligns with previous literature highlighting linezolid's potential to induce thrombocytopenia in neonates and pediatric populations [32][33][34]47]. Despite the widespread use of linezolid in clinical practice, there is no consensus on the incidence of its hematological toxicity in pediatrics, and the rates vary markedly from country to country, possibly due to ethnic differences [31][32][33][34].…”
Section: Discussionsupporting
confidence: 87%
“…The bactericidal activity of linezolid is time-dependent, trough concentrations ranging from 2-7 mg/L and/or an estimated 24-hour area under the curve over minimum inhibitory concentration (AUC 24 /MIC) of 80-120 mg•h/L are suggested as the therapeutic target range for linezolid [24][25][26][27]. Myelosuppression is one of the most serious reported adverse drug reactions for linezolid, both in adults and pediatrics [28][29][30][31][32][33][34]. Studies in adult populations showed that high trough concentrations (> 7.5 mg/L) are associated with an increased risk of linezolid-related hematologic adverse effects [22,26,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, SA-induced CAP is associated with unfavorable clinical outcomes compared to the common pneumococcal CAP, involving a higher risk for sepsis and septic shock, need for ICU-level care and organ function support, and significant mortality, regardless of the presence of methicillin-resistance ( 13 , 14 ). However, the current practice of empirical antimicrobial agents for MRSA-induced lung infections remains suboptimal in consideration of potential adverse drug reactions (ADRs) associated with first-line anti-MRSA antimicrobial agents, leading clinicians have to carefully weigh the pros and cons of antibiotic choices ( 15 , 16 ). This predicament underscores the pressing need for the development of new antibiotics, leading to the emergence of contezolid.…”
Section: Introductionmentioning
confidence: 99%